Optimization of photovoltaic module electrical characteristics using genetic algorithm - Muhammad Irwanto; Ismail, Daut, Prof. Dr.; Merdang, Sembiring, Dr. Ir.; Rosnazri, Ali; Dina Maizana, Maiz Ahmad (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.